Suppression of AGTR1 Induces Cellular Senescence in Hepatocellular Carcinoma Through Inactivating ERK Signaling - Wang, Houhong; Cui, Yayun; Gong, Huihui; Xu, Jianguo; Huang, Shuqin; Tang, Amao (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Cellular senescence is an effective barrier against tumorigenesis. Hence, it is of significance to characterize key features of cellular senescence and the induction of senescence in hepatocellular carcinoma (HCC) cells via pharmacological interventions. Our study determined the biological roles as well as mechanisms of angiotensin II type I receptor (AGTR1) on cellular senescence in HCC. Methods: Lentivirus vector-mediated overexpression or knockdown of AGTR1 was conducted in HCC cells, respectively. 8 μM sorafenib was used to induce cellular senescence, and ERK was activated by 30 ng/mL ERK agonist EGF. Proliferation was evaluated via clone formation assay. HCC cell senescence was examined by flow cytometry for cell cycle, senescence-associated β-galactosidase (SA-β-gal) staining, and senescence-associated heterochromatin foci (SAHF) analysis. AGTR1, p53, p21, extracellular signal-regulated kinase (ERK) and p-ERK expression was assessed through western blot or immunofluorescence. Results: AGTR1-knockout HCC cells displayed the attenuated proliferative capacity, G2-M phase arrest, increased expression of p53 and p21, elevated percentages of SA-β-gal- and SAHF-positive cells. In sorafenib-exposed HCC cells, overexpressed AGTR1 enhanced the proliferative capacity, alleviated G2-M phase arrest as well as decreased p53 and p21 expression and the proportions of SA-β-gal- and SAHF-positive cells. Moreover, AGTR1 knockdown attenuated the activity of p-ERK in HCC cells, and ERK agonist ameliorated AGTR1 knockdown-induced cellular senescence. Conclusion: This study demonstrates that suppression of AGTR1 induces cellular senescence in HCC through inactivating ERK signaling. The significant synergistic effect of AGTR1 suppression and sorafenib might represent a potential combination therapy for HCC.